2002
DOI: 10.1590/s0066-782x2002000100011
|View full text |Cite
|
Sign up to set email alerts
|

Primary coronary angioplasty in a nonagenarian

Abstract: A woman aged 98 years entered the tertiary hospital service with a picture of acute myocardial infarction of the extensive anterior wall, which began 4 hours earlier. Due to the large myocardial risk area suggested by the electrocardiogram, the patient was taken to the hemodynamics laboratory for the performance of emergency coronary arteriography, which revealed occlusion in the proximal third of the anterior descending artery. Primary angioplasty followed by stent grafting was successfully performed. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Even though primary PCI has been established as the standard of care, a conservative strategy is often adopted when facing this situation in nonagenarians 15 16. The first case report of primary PCI in a nonagenarian was published in 2002 17. Few studies based on cohorts have suggested feasibility for invasive management of STEMI in nonagenarians 18–21.…”
Section: Introductionmentioning
confidence: 99%
“…Even though primary PCI has been established as the standard of care, a conservative strategy is often adopted when facing this situation in nonagenarians 15 16. The first case report of primary PCI in a nonagenarian was published in 2002 17. Few studies based on cohorts have suggested feasibility for invasive management of STEMI in nonagenarians 18–21.…”
Section: Introductionmentioning
confidence: 99%